2016
DOI: 10.1200/jop.2016.015263
|View full text |Cite
|
Sign up to set email alerts
|

Current Role of Surgery in the Management of Oropharyngeal Cancer

Abstract: The 1990s saw an increased use of chemoradiotherapy protocols, commonly referred to as organ-sparing therapy, for the treatment of oropharyngeal cancer after the Groupe d’Oncologie Radiothérapie Tête Cou trial. Since that time, human papillomavirus–associated oropharyngeal squamous cell carcinoma has been identified as a unique disease, with improved survival regardless of treatment modality. The improved outcomes of this population has led to re-evaluation of treatment paradigms in the past decade, with a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…40,43 The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48-70), 66 (36-70), and 56 (45-66) grays (Gy). Treatment deintensification to reduce treatment toxicity while maintaining good oncologic outcomes are underway for both surgical [44][45][46][47] and nonsurgical 48,49 management of HPV-related OPSCC. During our study period, institutional deintensification strategies evolved toward eliminating radiation to the primary site in margin-negative resected T1 to T2 tumors, 50 and to the contralateral neck for well-lateralized tumors, 51 as well as reducing the ipsilateral radiation dose to 60 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…40,43 The median (range) adjuvant radiation dose at the primary, ipsilateral, and contralateral neck in our study cohort was 66 (48-70), 66 (36-70), and 56 (45-66) grays (Gy). Treatment deintensification to reduce treatment toxicity while maintaining good oncologic outcomes are underway for both surgical [44][45][46][47] and nonsurgical 48,49 management of HPV-related OPSCC. During our study period, institutional deintensification strategies evolved toward eliminating radiation to the primary site in margin-negative resected T1 to T2 tumors, 50 and to the contralateral neck for well-lateralized tumors, 51 as well as reducing the ipsilateral radiation dose to 60 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Existing treatment protocols for OPSCC were developed prior to HPV status consideration . With recent advancements in transoral surgery (including transoral robotic surgery and transoral laser microsurgery), there are increased efforts to manage HPV + OPSCC with surgery as the primary treatment to avoid or reduce radiation and chemotherapy toxicities . Several studies have demonstrated a better quality of life (QOL) in patients who underwent primary surgery for OPSCC .…”
Section: Introductionmentioning
confidence: 99%
“…However, the surgical patients were often p16 negative and treated before 2000, whereas the nonsurgical group was treated after 2000 with a much larger proportion of p16-positive patients. Several studies, based on single-center or multicenter evaluations of patient outcomes, have shown excellent oncological and functional outcomes with surgery for locally advanced OSCC [26,27]. However, the impact of HPV has not been emphasized in historic samples.…”
Section: Discussionmentioning
confidence: 99%